Trends and Patterns of Police Professional Misconduct in Nigeria: Analyses of Newspaper Reportage (2008-2018) - Ojedokun, Usman A.; Dinne, Chinedu E.; Ujene, Godspower I. (Journal of Applied And Theoretical Social Sciences, 2023)
Professional misconduct involving police officers has consistently put the Nigeria Police Force in a bad light and negatively impacts the public image of the law enforcement agency. In view of this, this study investigated incidents of police professional misconduct recorded in Nigeria between 2008 and 2018. Differential association theory and situational choice theory were employed as conceptual framework. Data were strategically elicited through content analysis of the online versions of three purposively selected first generation national newspapers in Nigeria. The results revealed that 137 cases of police professional misconduct were captured within the timeline. The highest percentage (32%) of the cases was reported in 2017 with Lagos State alone accounting for 29.9%. Furthermore, the involvement of police personnel in unethical behaviour was generally high in the last four months of every year. Extra-judicial killing (36.5%) was the most commonly reported type of police professional misconduct.